Enhancing fifth-grade reading skills through RADEC and QuizWhizzer - Ardita Putri Chahyani; Nur Latifah (Indonesian Journal of Educational Development (IJED), 2026)
Reading ability remains a major issue in Indonesian primary schools, as reflected in students' low performance on global literacy assessments. This issue is frequently related to teacher-centered education and insufficient utilization of engaging digital learning resources. This study examines the effect of integrating the RADEC learning model with the QuizWhizzer platform on fifth-grade students' reading comprehension. The research population comprised fifth-grade children at SDN Tengah 07 Jakarta, and saturation sampling was used, with all students serving as research participants and separated into an experimental and control group. Pretests and posttests were administered using multiple-choice reading comprehension test instruments that included literal, inferential, critical, and creative features. Due to non-normal data distribution, the Wilcoxon signed-rank test was applied for analysis. The findings indicate improvement in both groups, with significantly greater gains in the experimental group. These findings demonstrate the usefulness of integrating structured learning models with interactive digital media in increasing engagement and understanding through active involvement and collaboration. Future research should investigate larger samples and longer implementation periods, as well as the incorporation of comparable digital platforms, to increase reading instruction in elementary school.